(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Owing to the increasing depletion of nonrenewable resources and effects produced by global warming, the high levels of energy consumption and pollution generated during the production of cement clinker have attracted widespread concern. Utilization and recycling of industrial waste and by-products to prepare building materials is the green style and contributes to the resource conservation and environmental protection. Recovering solid waste represents one of the major methods for manufacturing such “green” cementitious materials. Hence in this work, an experimental investigation on mine filling materials preparation using fly ash, carbide slag, FDCG (Flue-Gas Desulphurisation) gypsum and GBF (Granulated Blast-Furnace Slag. Environmentally friendly and cheap composite green cementitious materials have been prepared from carbide slag, fly ash and flue gas desulphurisation Gypsum (FGDG) and Granulated Blast-Furnace without using cement clinker. This work investigates the effects of the raw materials on the amount of water required for reaching standard consistency, slump value, and strength of the produced materials after curing for 7 d and 28 days. Scanning Electron Microscopy (SEM) and X-ray diffraction (XRD) techniques are used to analyze the sample microstructure and hydration products as well as for the exploration of possible hydration mechanisms.